ECONOMIC GROWTH AND ENVIRONMENTAL MANAGEMENT IN THE MANUFACTURING INDUSTRIES OF ECUADOR. STRATEGIES TOWARDS A CIRCULAR ECONOMY MODEL - Aldas Salazar, Darwin (2022)
One of the Sustainable Development Goals (SDG) promoted by the United Nations is responsible production and consumption through the efficient use of energy, contributing to the maximization of environmental benefits andminimization of resource use, contributing to sustainable development in order to counteract the consequences of the linear production model. That is why in the present research the gap between economic growth and environmental management was analyzed, as well as its degree of correlation and causality in the manufacturing industries of Ecuador. For the development of this study, the economic growth trend of the sector and theevolution of environmental management evaluated between 2016 to 2020 and the projected perspectives to 2022 are observed. National databases validated through the Ecuadorian Institute of Statistics and Census (INEC) were used for the analysis. Data were analyzed using RStudio software through time series and ARIMA models with Dickey-Fuller stationarity tests, white noise tests with Ljung Box Test and correlation studies with Pearson’s R test. The results obtained show the current economic and environmental situation of the manufacturing industry,as well as its prospects and growth trends towards a sustainable production model. Finally, strategies that could be adopted by industries to enter into a circular economy and sustainability model are proposed.